2020
DOI: 10.21203/rs.2.13789/v6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The functions of ocu-miR-205 in regulating hair follicle development in Rex rabbits

Abstract: Background: Hair follicles is an appendage from the vertebrate skin epithelium, and arise from the embryonic ectoderm andregenerate cyclically during adult life. Dermal papilla cells (DPCs) is the key dermal component of the hair follicle that directly regulates hair follicle development, growth and regeneration. Recent studies have reported that miRNA plays an important role in regulating hair follicle morphogenesis, proliferation, differentiation and apoptosis of hair follicle stem cells. Results: The miRNAs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These lncRNAs and genes might play crucial roles in regulating hair follicle density, and their differential expression might be the reason for differences in hair follicle density and wool production between HWP and LWP rabbits. Liu et al (2020) analysed the miRNA effect on hair follicle density in the Rex rabbit [37], but lncRNA related to hair density in rabbits has only been done in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These lncRNAs and genes might play crucial roles in regulating hair follicle density, and their differential expression might be the reason for differences in hair follicle density and wool production between HWP and LWP rabbits. Liu et al (2020) analysed the miRNA effect on hair follicle density in the Rex rabbit [37], but lncRNA related to hair density in rabbits has only been done in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there is a direct relationship between the Notch signal pathway and hair follicle morphogenesis [47], high expression of Notch1 and Notch2 can accelerate the formation of mouse hair substrate and, at the same time, it can inhibit the cells around hair substrate to form substrate [48]. Ocu-miR-205 can promote the transition of Rex rabbit hair follicles from the growing stage to a degenerative quiescent stage by regulating the expression of related genes and proteins in Notch, BMP and other signal pathways,changing the hair density [49]. Krieger et alused mice model to study the regulation of the NF-kb signal pathway in the hair follicle cycle, and found that the NF-kb signal pathway is essential for the growth and activation of hair follicle stem cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…The fur quality index in different ages of Rex rabbit detection method as described previously [13]. The adhesive tissue and fat was removed from fur, and weighed, then cut in the middle of the abdomen, and the length and width of the skin were measured using a soft ruler.…”
Section: Fur Qualitymentioning
confidence: 99%